Shock Waves - Mignault, Pierre; Magny, Hélène (Barton, Nathalie, 2007)
Verzio FF submission Despite the signed peace accords of 2003, millions continue to die in the troubled Democratic Republic of Congo, home to some of the worst human rights violations in the world. But there is a ray of hope. Radio, once a means for spreading propaganda and hatred, is now being used as a tool for justice and truth. For six years internationally funded independent Radio Okapi has been broadcasting from the frontlines and giving the Congolese people a voice. Under the constant threat of violence and death for their critiques of those in power, more than 100 journalists from Radio Okapi expose injustice and corruption wherever they find it. Its existence has become a lifeline for the people, offering hope of a future with unity and peace.